1998
DOI: 10.1046/j.1365-3024.1998.00149.x
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of cattle against the Boophilus microplus using a mucin‐like membrane glycoprotein

Abstract: An antigen, BMA7, which induced partial immunity against tick infestation has been isolated from Boophilus microplus using two different protein fractionation protocols, accompanied by vaccination and parasite challenge trails. The antigen is a 63 kDa glycoprotein isolated from semi-engorged adult female ticks. Though significant, the induced immunity is less striking than that previously reported for antigen Bm86 from the same parasite. However, co-vaccination with Bm86 and BMA7 can enhance immunity over that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 18 publications
0
20
0
1
Order By: Relevance
“…Also of interest as targets for vaccine development are components derived from the midgut. Three membrane-bound glycoproteins -the carboxydipeptidase Bm91 and two proteins of unknown function, Bm86 and BMA7, were isolated from midgut preparations of R. microplus and elicited protection when used for vaccinating cattle (Riding et al, 1994;Willadsen et al, 1995;McKenna et al, 1998). Based on the Bm86 molecule, the recombinant commercial vaccine TickGARD was developed (Willadsen, 2004), which reduces survival and reproduction rates of ticks.…”
Section: Introductionmentioning
confidence: 99%
“…Also of interest as targets for vaccine development are components derived from the midgut. Three membrane-bound glycoproteins -the carboxydipeptidase Bm91 and two proteins of unknown function, Bm86 and BMA7, were isolated from midgut preparations of R. microplus and elicited protection when used for vaccinating cattle (Riding et al, 1994;Willadsen et al, 1995;McKenna et al, 1998). Based on the Bm86 molecule, the recombinant commercial vaccine TickGARD was developed (Willadsen, 2004), which reduces survival and reproduction rates of ticks.…”
Section: Introductionmentioning
confidence: 99%
“…However, the success of this method depend on the identification, cloning, and in vitro expression of tick molecules playing key physiological roles in the biological success of the tick as a vector and pest [4,13,20]. Mulenga et al [14] demonstrated the possibility of a tick vaccine against H. longicornis.…”
mentioning
confidence: 99%
“…Although the vaccine efficacy for controlling immature B. microplus is uncertain, the Bm86 vaccine clearly demonstrated that targeting the tick gut alone can cause severe damage to the tick. The vaccine can be further improved when used in combination with other concealed antigens, such as Bm91 and BMA7 [59,60]. Bm91 is a carboxydipeptidase, largely concentrated in the salivary glands [61].…”
Section: New Strategy For Anti-tick Vaccine Developmentmentioning
confidence: 99%
“…Bm91 is a carboxydipeptidase, largely concentrated in the salivary glands [61]. Antigen BMA7 is a mucin-like membrane glycoprotein widely distributed in the tick body [60]. Vaccination using Bm91 or BMA7 alone was not as effective as the Bm86 vaccine, but combinations with Bm86 significantly enhanced vaccine efficacy.…”
Section: New Strategy For Anti-tick Vaccine Developmentmentioning
confidence: 99%